Light quality on growth and phenolic compounds accumulation in Moringa oleifera L. grown in vitro - da Silva, Raphael Reis; Ribeiro de Souza, Rafaela; Coimbra, Mairon; Nery , Fernanda; Alvarenga, Amauri; Paiva, Renato (Comunicata Scientiae, 2020)
All plant parts of the Moringa oleifera can contain relevant concentrations of phytochemicals with health benefits. Plants grown in vitro allow pathogen-free plant material production and rapid propagation, and this technique is widely used to obtain secondary metabolites. This study analyzed how light spectrum quality affects growth, chlorophyll, and total phenolic content in M. oleifera plants grown in vitro. M. oleifera seeds were inoculated in MS medium supplemented with 3% sucrose and 0.7% agar and were stored under a controlled temperature, humidity and photoperiod. The light conditions tested were white fluorescent lamps (WFL) and light-emitting diodes (LED: 70% red + 30% blue), both standardized with a photon flux density of 58 μmol m-2s-1. Radiation emitted by WFL and LED did not influence stem germination, height, or diameter. However, WFL provided higher total chlorophyll levels. All plant parts germinated in vitro were analyzed via high-performance liquid chromatography with a diode-array detector (HPLC-DAD), and preliminary analyses revealed preferential synthesis of gallic acid derivatives in the leaves under LED radiation. For the total phenolic content, leaves under the LED and WFL irradiations showed 3.524 ± 0.054 and 3.805 ± 0.304 micrograms, respectively, of gallic acid equivalents per milligram of dry matter (μg GAE mg-1 DM). Light quality did not interfere with phenolic compound accumulation; however, it stimulated the preferential synthesis of gallic acid derivatives in leaves grown under LED radiation, and the evidence indicated that all evaluated organs synthesized nonpolar substances.